Georreferenciamento e estudo clínicoepidemiológico dos acidentes escorpiônicos atendidos em Belo Horizonte, no serviço de toxicologia de Minas Gerais - Delio Campolina (2006)
Clinical and epidemiological aspects of 1143 scorpion sting accidents attended in the year of 2004 at João XXIII Hospital, Toxicology Service of Minas Gerais State (Poisoning Control Center) are described and matched with Health Institution data in an epidemiological cross-sectional study. The hospital is a regional referralcenter for emergencies, burns, poisonings and venomous animals accidents. Scorpion sting is a public health problem in the metropolitan area of Belo Horizonte city. 942 of the studied scorpion stings were attended at hospital. The others 201 cases were from smaller cities from the metropolitan area and other cities with remote attendance by poisoning control center information section. Among hospital attended patients 627 occurred in Belo Horizonte and 315 in cities of the metropolitan area. Also, regional notifications from all Brazilian States were studied and matched with local data. A temporal geographic and density study with the stings address from Belo Horizonte using HOTSPOT DETECTIVE for MAPINFO, version 1.3 was made. About 47% of patients brought the scorpions to the hospital which were identified as Tityus serrulatus Lutz e Mello, 1822 (99.1), Tityus bahiensis Perty, 1833 (0.7) e Tityus adrianoi Lourenço, 2003 (0.2) %. Most of the cases occurred between August and March as happened with national datafor Southeast Region. Most of the cases occurred inside home (75,3%). The locations of the stings were the hands (29.2%), feet (22.4%) and hand fingers (13.2%). Local signs were presented in 98.1% of cases and systemic manifestations in 17%. Most of the attendance occurred after one hour of accident (5.91%) with median of 60 minutes. 4.9% of patients used scorpion antivenom; 91.3% of them receiving four or less flasks and only 2.2% had an early anaphylactic reaction. Children and teenagers under 15 years old had about 11 times more needs of specific serumtherapy. (p<0.001; OR 10.904; IC95% = 5.699 xxv 20.861). National analysis results showed lethality of 0.15 %; Death risk of agroup constituted by patients under 15 years old was 18 times bigger than age 15 or over (p<0.0000001; OR = 18.32; IC95% = 7.41 48.25); 14 deaths occurred in patients attended before one hour elapsed from sting to death, but a double risk of death in the group attended after three hours. Minas Gerais and Bahia States were responsible for 63 % of deaths and 43 % of related stings in 2004. Using both national and local cases the analysis showed: no differences in lethality (p = 0.6483); mild and severe classification of cases were 15 times bigger in Brazil cases (p<0.0000001; OR = 14.58; IC = 10.02 21.26). Spatial distribution of89.93% of point events of scorpionism among regions of Belo Horizonte City, showed bigger incidence in the regions of Northeast and Norwest, statistically similar among themselves. They were followed by Pampulha and then West and North Regions. In conclusion it was shown that there are differences among regions in Brazil; the immediate attendance is important; serumtherapy is well tolerated; childhood and teenagers under 15 years old represent a group of high risk; in several cases severity was not avoided by serumtherapy, even when used before one hour after sting; there are specific Regions in Belo Horizonte with accident bigger incidence.